Persepsi Remaja Terhadap Gambar Bahaya Merokok Pada Bungkusnya Di Indonesia - Sholeh Fikri; Yuli Syahfitri (IAIN Padangsidimpuan, 2025)
The objective of this study is to understand the perceptions of teenage smokers toward the warning images on cigarette packaging, as well as to identify the factors that influence their continued smoking behavior despite the presence of such visual health warnings. This study employs a qualitative research design using a descriptive approach. The data sources consist of both primary and secondary data. Data collection techniques include observation, interviews, and documentation. The research was conducted in the city of Padangsidimpuan, North Sumatra, from July to November 2021. Field findings indicate that the teenagers are aware that smoking is considered religiously prohibited, as it is harmful and regarded as wasteful behavior. Further results show that 40% of the teenagers believe that the warning images on cigarette packages are merely intended to frighten people or may only be relevant after a long period of time, and even then, only if the smoker has a weak physical condition. Meanwhile, 20% of the teenagers think the warnings are untrue because they have never experienced any serious health issues as depicted in the images. Another 30% view the warning labels as overly dramatic and exaggerated. These perceptions are among the contributing factors that lead teenage smokers to continue their smoking habits. Lastly, 10% of respondents stated that the warning images serve only as additional information, but do not influence or change their behavior.